A Study of the Balongo and its Implications for Interfaith Dialogue in the Church of Uganda - Susan, Kemigisha (Advances in Social Sciences Research Journal, 2025)
This thesis explores the intersection of ancestral spirit worship and Christianity in Buganda, Uganda, with a specific focus on the concept of Balongo (ancestral spirits) and its implications for interfaith dialogue and religious studies. The study employs a qualitative research design, utilizing in-depth interviews, focus groups, and observational studies to collect data. The findings highlight the cultural significance of Balongo spirits in Luganda cosmology, the complex and dynamic relationship between Balongo and Christianity, and the potential for interfaith dialogue and cooperation. The research contributes to a deeper understanding of the intersections between traditional religiosity and Christianity in Africa, highlighting the need for greater contextualization of Christian theology and practice, and promoting greater understanding and respect between practitioners of traditional religiosity and Christianity. The study’s findings have significant implications for Christian theology and practice, interfaith dialogue, and cooperation in Uganda and beyond.